THE SEA, THE VOLCANO, AND THE TIGER: SOME ANIMISTIC SYMBOLS IN ORAL TRADITION AND MODERN INDONESIAN LITERATURE - Frolova, Marina (Sanata Dharma University, 2017)
The article deals with the idea of rediscovering three basic images of Indonesian culture: the sea, the volcano and the tiger, with the help of folklore and splendid literary works of modern Indonesian writers as well. Novels by Mochtar Lubis (Harimau! Harimau! 1975), Eka Kurniawan (Lelaki Harimau, 2004), and Budi Sardjono (Sang Nyai, 2011) are taken as a source. The enriched traditional meanings of some animistic symbols appear in different light in each novel, rediscovering the layers of main plot and characters connotations in different ways of Neo-Traditionalism, Deconstruction and Remythologization.Â DOI: https://doi.org/10.24071/ijhs.2017.010103